Trends in Abdominal Obesity and Central Adiposity Measures by Dual-Energy X-Ray Absorptiometry Among US Children: 2011–2018 - Liu, Jiahui; Zhao, Yue; Tian, Yalan; Jiang, Nana; Zhao, Gang; Wang, Xia (Frontiers in Pediatrics, 2022)
Objective: Previous studies that have reported trends on abdominal obesity among US children were usually based on anthropometric assessments. However, little is known about the recent trends in central adiposity measures by DXA and abdominal obesity since 2011 to 2012. Study design: A serial cross-sectional analysis of US population-weighted data among children from NHANES 2011 to 2018 was conducted. Results: Between 2011–2012 and 2017–2018, there was a relatively stable trend among children aged 8 to 19 years in trunk fat and trunk fat percentage. During the same time periods, there were no significant changes in prevalence of abdominal obesity by waist circumference (18.6% vs 21.1%) among those aged 2 to 19 years, and abdominal obesity by WHtR (34.1% vs 36.2%) among those aged 6 to 19 years. However, a significant increase trend among boys aged 2 to 19 years was found in prevalence of abdominal obesity by waist circumference (16.1% to 22.7%; P = 0.004). For Mexican American youth and non-Hispanic Asian boys, there is a significant increase in mean trunk fat percentage and waist circumference. Conclusion: Between 2011–2012 and 2017–2018, there have been no significant changes in central adiposity measured by DXA and prevalence of abdominal obesity among US children. Our study further supports that there is an urgent need to improve their lifestyle to reduce abdominal obesity for US children, especially for Mexican American youth and non-Hispanic Asian boys.